Income and longevity revisited: Do high-earning women live longer? - Friedrich Breyer; Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The empirical relationship between income and longevity has been addressed by a large number of studies, but most were confined to men. In particular, administrative data from public pension systems are less reliable for women because of the loose relationship between own earnings and household income. Following the procedure first used by Hupfeld (2010), we analyze a large data set from the German public pension scheme on women who died between 1994 and 2005, employing both non-parametric and parametric methods. To overcome the problem mentioned above we concentrate on women with relatively long earnings history. We find that the relationship between earnings and life expectancy is very similar for women as for men: Among women who contributed at least for 25 years, a woman at the 90th percentile of the income distribution can expect to live 3 years longer than a woman at the 10th percentile.
Keywords: I12; H55; 330; Life expectancy and income; women; public pensions; Germany; Sterblichkeit; Einkommensverteilung; Frauen; Gesetzliche Rentenversicherung; Deutschland